Digitizing of User Activity Settings in Alun-alun Kauman Semarang - Kinasih, Kania; Purwanto, L.M.F (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2024)
The function of the Alun-alun as a public space was originally to accommodate state ceremonial activities and religious rituals. Slowly the function of the Alun-alun also changed according to the times. This diverse function of the Alun-alun also still applies in Alun-alun Kauman and becomes more complex with the addition of other functions due to the dynamics of development that occur. The current function of Alun-alun Kauman is to accommodate three main activities, namely sports activities, recreational activities, and religious ritual activities, which are supported by trading activities. This research aims to find the activity order of Alun-alun Kauman users in the new design. The method used was a quantitative approach. Data collection techniques were conducted through field observations in a full day for one week. The time span of a day was broken down into 2-hour intervals. This is based on the consideration that the average visitor activity time ranges from 1 to 2 hours. Data quantification and analysis are based on observations of visitor activity settings. Digitization is an effort to utilize applications or software used as research aids, by translating quantitative data into graphics. Through the digitization picture, the data of visitor activity order can be seen quickly, easily, and accurately. It was found that the Alun-alun as a public space has a function that is still in demand by local residents to conduct activities.